Salivary duct carcinoma: Correlation of morphologic features by fine needle aspiration cytology and histopathology - N G Rajesh; Aruna K Prayaga; C Sundaram (Wolters Kluwer Medknow Publications, 2011)
Background: Salivary duct carcinoma (SDC) is a highly aggressive primary salivary gland neoplasm that resembles intraductal and infiltrating breast carcinoma. Objectives: To review cytomorphologic features of histology proven SDC and evaluate potential pitfalls in cytologic diagnosis. Materials and Methods: Fine needle aspiration cytology (FNAC) of five histologically proven SDCs were reviewed. Results: One patient was an elderly male (61 years), while the other four patients were younger, in their fourth decade (average age: 38 years). The initial cytologic diagnoses in two of the cases were poorly differentiated carcinoma with differential diagnosis of SDC and high grade mucoepidermoid carcinoma, while in the third case, a possibility of malignant mixed tumor was suggested. In fourth and fifth cases, the diagnosis was suggestive of pleomorphic adenoma with cystic change. The spectrum of cytologic changes included flat sheets and cohesive papillary and three-dimensional clusters. There was moderate to severe nuclear pleomorphism and atypia. Cribriform pattern and necrosis were occasionally identified. Prominent bright granular metachromatic stroma was seen in two of the cases interpreted as pleomorphic adenoma with cystic change and in the tumor reported as suggestive of malignant mixed tumor. The fifth case showed numerous cyst macrophages and apocrine cells with mild nuclear atypia. Conclusion: FNAC of SDC is difficult to interpret because of overlapping cytomorphologic features. Bland cytomorphologic features in some cases and several clinical pitfalls are demonstrated in our series.